Isolation and Antibiotic Resistance of Helicobacter pullorum from Chicken Wings - Hosein Akhlaghi; Seyed Hesamodin Emadi Chashmi; Ashkan Jebelli Javan (Journal of Fasting and Health, 2021)
Introduction: Helicobacter pullorum has recently emerged as a significant foodborne pathogen. The present study aimed to isolate and determine the antibiotic resistance of H. pullorum from fresh chicken wing using the culture method and a molecular technique in Semnan, Iran. Methods: A total of 60 fresh chicken wings samples were purchased from various local retail markets in different regions of Semnan and processed using the culture method. For initial confirmation, biochemical tests were applied. Suspected colonies were subjected to polymerase chain reaction (PCR) by the 16S rRNA gene. The antibiotic resistance of the isolates was also assessed using the disk-diffusion method. Results: Among 60 samples, 27 (45%) were H. pullorum-positive based on the culture method and biochemical tests. However, the PCR test indicated 18 samples (30%) to be positive for H. pullorum. In the antibiogram, the highest and lowest resistance rates were observed against ciprofloxacin and fosfomycin, respectively. Conclusion: This was the first report in Iran to clearly illustrate that H. pullorum could be found in fresh chicken wings at a moderate level. In addition, the antibiotic resistance of the H. pullorum isolates was confirmed, and the PCR test based on the 16S rRNA gene was considered a reliable and sensitive technique for the detection of this pathogen. However, further investigation is required to explore the life cycle of this novel foodborne pathogen in the other regions of Iran.